Estudo de tensões e modos de falha no desenvolvimento de adesivos nanomodificados e juntas coladas - Almir Silva Neto (2016)
Until recently, the use of high performance composite materials was restricted to a few high-tech industries, mainly for financial reasons. However, with the technological de-velopment of manufacturing processes and the factories access to industrial robots, this reality is changing. The use of conventional methods for joining composite materi-als is not indicated. The non-isotropic nature of these materials enhances the negative effects introduced by stress concentrators derived by holes and cuts for using bolts, rivets, among others. To adequately tackle this problem, adhesive joints are studied for use in the design of structures that are assembled by joining parts. This work relates nanomodified adhesive stresses on single-lap joints, with and without UV aging, with their respective strengths. The newly made adhesives showed an increase of up to 4.1% in Youngs module and 2.5% in hardness compared to the unmodified adhesive. Joints bonded with the modified adhesives had a 6% increase in resistance. UV deg-radation effects in the adhesive was evaluated by FTIR. A relationship between the stresses in the nanomodified adhesives used in single-lap joints and exposure to ul-traviolet radiation was established. This relationship is established between the stress gradient variation in thickness direction of adhesives with different concentrations of graphene (the observed increase was up to 16.7%) and failure modes coming from destructive testing (which predominated mixed failure modes with the prevalence of cohesive failure). Therefore, a design method that increases joints load capacity by combining two established techniques was proposed. The efficacy of the method was verified by finite element analysis. An increase in the rotational stiffness of the joint, measured by the reduction of the rotation angle in 14.8%, leads to stress reliefs in the adhesive and the consequent increase in resistance.